Adolescents’ perspectives on non-pharmacological pain interventions for sickle cell crisis management: A population-based survey - Bukola Mary Ibitoye; Bernie Garrett; Manon Ranger; Jennifer N. Stinson (PLoS ONE, 2025)
Background & Aims Nigeria has the highest sickle cell disease (SCD) prevalence globally. Research indicates that adolescents often utilize non-pharmacological interventions (NPIs) to cope with recurrent painful sickle cell crises (SCC) while navigating the complex biopsychosocial challenges of adolescence. This study explored the use and perceived value of NPIs for managing SCC pain from the perspectives of Nigerian adolescents, including their preferred media for NPI educational resources. Methods A population-based survey targeted adolescents aged 12–18 living with SCD in Nigeria. Adolescents were recruited using convenience and snowballing sampling through SCD support groups and were asked to complete a 27-item questionnaire delivered online or on paper. Data were descriptively analysed. Results Out of 138 surveys returned, 123 surveys were included in the final analysis. Among the participants, 51% were males with a mean age of 14.85 (SD ± 2.11). Most participants (77%) had used at least one NPI to manage pain during SCC, and 31 different NPIs were reported. The most used NPIs were massage (53%), herbal products (37%) and prayer (30%). Participants described various factors that impacted their use of NPI, including healthcare providers’ disapproval. The most common NPIs that the adolescents plan to use in the future were: herbal products (45%), massage (33%) and prayer (30%). Lastly, respondents preferred to receive NPI education via videos (34%) and animations (20%). Conclusions The study showed that Nigerian adolescents use various NPIs to manage their pain during SCC, including traditional remedies and physical and spiritual interventions. Most participants already used (or planned to use) herbal products and other NPIs with limited scientific evidence of their safety or effectiveness on SCD outcomes. This warrants the attention of clinicians and researchers as there is an urgent need to further explore the specific NPIs used and their effectiveness on SCD outcomes and safety.